Humanitarian Crises and Migration: causes, consequences and responses.: Susan Martin; Sanjula Weerasinghe; Abbie Taylor (org.). London / New York, Routledge, 2014, 375 p. - Dornelas, Sidnei Marco (TRAVESSIA - revista do migrante, 2015)
[...]